Prognosis of the end-of-life of lithium iron phosphate batteries with application in large-scale electric buses - Poonah, Brandon (Stellenbosch : Stellenbosch University, 2025)
Poonah, B. 2025. Prognosis of the End-of-Life of Lithium Iron Phosphate Batteries with application in Large-Scale Electric Buses. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/dfb789a0-cdce-49d7-8c4e-ec7d4c897bd6